Paediatric COVID‐19 admissions in a region with open schools during the two first months of the pandemic. (7th July 2020) - Hildenwall, Helena; Luthander, Joachim; Rhedin, Samuel; Hertting, Olof; Olsson‐Åkefeldt, Selma; Melén, Erik; Alfvén, Tobias; Herlenius, Eric; Ryd Rinder, Malin
Abstract :